Effect of different doping ratios of Mo doping and Zn vacancy on magneto-optical properties of ZnO. (May 2021) - Sha, Shulin; Hou, Qingyu; Liu, Yajing; Xu, Zhenchao
Abstract: The source of ZnO magnetism in Mo doping and Zn vacancy is not fully understood. Generalized gradient approximate plane wave ultrasoft pseudopotential method was adopted based on the spin density functional theory to solve this problem. The structural stability and magneto-optical properties of Mo doping and Zn vacancy in co-existing ZnO were calculated using the first principle. The band gap of the doping system is narrower than that of the pure ZnO, and the absorption spectrum showed a red shift in the visible light range of 380–600 nm. The Zn34 MoO36 had the strongest absorption spectrum intensity, the most significant red shift phenomenon, the easiest electron and hole separation, and the strongest photocatalytic activity. These features are beneficial to the design and preparation of new photocatalysts. When Mo to Zn vacancy ratio of 2:2, the Zn32 Mo2 O36 has the strongest magnetic properties, and the electron spin polarization was 100%, which is advantageous for designing and preparing the dilute magnetic semiconductors. The Zn32 Mo2 O36 has shown room temperature ferromagnetism, and the magnetism of the Zn32 Mo2 O36 came from the hole produced by Zn vacancy. Double exchange interaction occurred between non-pairing itinerant electron in the O–2P orbit near the Zn vacancy and the spin polarization of electrons in Mo-4d orbitals with the hole as a medium. This is consistent with the mean field approximation and the double exchange mechanism theory. Highlights: Effect of different doping ratios of Mo doping and Zn vacancy on magneto-optical properties of ZnO. All doping systems occurred red shift in the absorption spectra in the wavelength range of 380–600 nm. Zn34 MoO36 has the highest photocatalytic activity. Zn32 Mo2 O36 has the strongest magnetic properties and electron spin polarization is 100%.